Reversible Control of Gelatin Hydrogel Stiffness by Using DNA Crosslinkers. (25th February 2021) - Buchberger, Alex; Saini, Harpinder; Eliato, Kiarash Rahmani; Zare, Azadeh; Merkley, Ryan; Xu, Yang; Bernal, Julio; Ros, Robert; Nikkhah, Mehdi; Stephanopoulos, Nicholas
Abstract: Biomaterials with dynamically tunable properties are critical for a range of applications in regenerative medicine and basic biology. In this work, we show the reversible control of gelatin methacrylate (GelMA) hydrogel stiffness through the use of DNA crosslinkers. We replaced some of the inter‐GelMA crosslinks with double‐stranded DNA, allowing for their removal through toehold‐mediated strand displacement. The crosslinks could be restored by adding fresh dsDNA with complementary handles to those on the hydrogel. The elastic modulus (G') of the hydrogels could be tuned between 500 and 1000 Pa, reversibly, over two cycles without degradation of performance. By functionalizing the gels with a second DNA strand, it was possible to control the crosslink density and a model ligand in an orthogonal fashion with two different displacement strands. Our results demonstrate the potential for DNA to reversibly control both stiffness and ligand presentation in a protein‐based hydrogel, and will be useful for teasing apart the spatiotemporal behavior of encapsulated cells. Abstract : Going soft : We report a gelatin methacrylate hydrogel crosslinked with DNA. The stiffness of the gel can be switched by a factor of ∼2, over two cycles, by using displacement strands, with no degradation of gel performance. Using two DNA sequences allows orthogonal control of gel stiffness and ligand presentation.